DEVELOPING AN ENGLISH TEXT BOOK BASED ON PROBLEM SOLVING APPROACH FOR FIFTH GRADE STUDENT OF SDN SALEN - Beny Arihakam Hakam (JETS, English Department of University of Uluwiyah Mojokerto, 2023)
Abstract: Teaching English at elementary school, usually students study about simple words or things in student surroundings, it is aimed that students are able to understand simple English used in daily activity like study number, animal, color and part of body. However, it is difficult to master the other competences without understanding English, because English is the basic competence that must be reached by students in order to get other competencies like reading, writing, listening, and speaking. The researcher would like to develops an English the text book with picture series based on Problem Solving Approach likes ; tourist object in Mojokerto, daily activity, food and drink, transportation, profession make easy to understand for fifth grade at elementary school. The objectives of the study ,To describe the target needs of the students grade fifth of elementary school, the object of this study is aim to produce text book based on Problem Solving Approach, To develop text book based on Problem Solving approach at SDN Salen, The design of this research R & D ( Research and Development). Based on its purpose, this research is classified into research and development study. This research is undertaken to develop text book for fifth grade at SDN Salen. The product of this study was picture series English material for fifth grade students of SDN Salen, Bangsal , Mojokerto for even semester. It was complete with teacher guide is use the teaching or instruction method to use the material.